Virtual Reality Objectifies the Diagnosis of Psychiatric Disorders: A Literature Review - van Bennekom, Martine J.; de Koning, Pelle P.; Denys, Damiaan (Frontiers in Psychiatry, 2017)
Background To date, a diagnosis in psychiatry is largely based on a clinical interview and questionnaires. The retrospective and subjective nature of these methods leads to recall and interviewer biases. Therefore there is a clear need for more objective and standardized assessment methods to support the diagnostic process. The introduction of Virtual Reality (VR) creates the possibility to simultaneously provoke and measure psychiatric symptoms. Therefore, VR could contribute to the objectivity and reliability in the assessment of psychiatric disorders. Objective In this literature review we will evaluate the assessment of psychiatric disorders by means of VR environments. First, we investigate if these VR environments are capable of simultaneously provoking and measuring psychiatric symptoms. Next, we compare these measures with traditional diagnostic measures. Methods We performed a systematic search using Pubmed, Embase and Psycinfo; references of selected articles were checked for eligibility. We identified studies from 1990-2016 on VR used in the assessment of psychiatric disorders. Studies were excluded if VR was used for therapeutic purposes, if a different technique was used or in case of limitation to a non-clinical sample. Results A total of 39 studies were included for further analysis. The disorders most frequently studied included schizophrenia (n=15), developmental disorders (n=12), eating disorders (n=3) and anxiety disorders (n=6). In ADHD the most comprehensive measurement was used including several key symptoms of the disorder. Most of the studies however concerned the use of VR to assess a single aspect of a psychiatric disorder. Discussion In general, nearly all VR environments studied were able to simultaneously provoke and measure psychiatric symptoms. Furthermore, in 14 studies significant correlations were found between virtual reality measures and traditional diagnostic measures. Relatively small clinical sample sizes were used, impeding definite conclusions. Based on this review, the innovative technique of virtual reality shows potential to contribute to objectivity and reliability in the psychiatric diagnostic process.